Cellular immune activity biomarker neopterin is associated hyperlipidemia: results from a large population-based study. Issue 1 (December 2016) - Chuang, Shu-Chun; Boeing, Heiner; Vollset, Stein; Midttun, Øivind; Ueland, Per; Bueno-de-Mesquita, Bas; Lajous, Martin; Fagherazzi, Guy; Boutron-Ruault, Marie-Christine; Kaaks, Rudolf; Küehn, Tilman; Pischon, Tobias; et al.
Abstract Background Increased serum neopterin had been described in older age two decades ago. Neopterin is a biomarker of systemic adaptive immune activation that could be potentially implicated in metabolic syndrome (MetS). Measurements of waist circumference, triglycerides, high-density lipoprotein cholesterol (HDLC), systolic and diastolic blood pressure, glycated hemoglobin as components of MetS definition, and plasma total neopterin concentrations were performed in 594 participants recruited in the European Prospective Investigation into Cancer and Nutrition (EPIC). Results Higher total neopterin concentrations were associated with reduced HDLC (9.7 %, p < 0.01 for men and 9.2 %, p < 0.01 for women), whereas no association was observed with the rest of the MetS components as well as with MetS overall (per 10 nmol/L: OR = 1.42, 95 % CI = 0.85-2.39 for men and OR = 1.38, 95 % CI = 0.79-2.43). Conclusions These data suggest that high total neopterin concentrations are cross-sectionally associated with reduced HDLC, but not with overall MetS.